1997
DOI: 10.1177/00957984970234002
|View full text |Cite
|
Sign up to set email alerts
|

An Afrocultural Social Ethos: Component Orientations and Some Social Implications

Abstract: Two studies explored an Afrocultural social ethos: its component orientations of spirituality, affect, and communalism; and their connections with psychosocial functioning among inner-city African American youth in Grades 5 through 7. Positive endorsement and moderate positive correlations among the orientations were found in each study. In Study 1, an Afrocultural social ethos was predictive of more cooperative and more competitive academic attitudes and lower levels of a Machiavellian attitude. When orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…A number of developmental assets related to race and ethnicity are unique to youth of color. For example, among African American youth, racial identity is positively related to self‐esteem (Rowley, Sellers, Chavous, & Smith, 1998; Sellers, Copeland‐Linder, Martin, & Lewis, 2006) and academic achievement (Jagers, Smith, Mock, & Dill, 1997). However, few studies beyond the literature on racial identity have recognized the relation of these cultural assets to positive developmental outcomes outside of a risk‐based perspective.…”
Section: Positive Development Of African American Youthmentioning
confidence: 99%
“…A number of developmental assets related to race and ethnicity are unique to youth of color. For example, among African American youth, racial identity is positively related to self‐esteem (Rowley, Sellers, Chavous, & Smith, 1998; Sellers, Copeland‐Linder, Martin, & Lewis, 2006) and academic achievement (Jagers, Smith, Mock, & Dill, 1997). However, few studies beyond the literature on racial identity have recognized the relation of these cultural assets to positive developmental outcomes outside of a risk‐based perspective.…”
Section: Positive Development Of African American Youthmentioning
confidence: 99%
“…Models of racial/ethnic identity were developed which suggest that individuals move from having naïve beliefs about their racial group status, holding negative feelings about their racial group, or placing low salience on race, to developing racial consciousness and a sense of pride in history, heritage, and group membership (Schwarzbaum and Thomas 2008). Positive racial identity has been found to be related to positive outcomes in African American youth, including positive self-esteem (Buckley and Carter 2005;Greene et al 2006;Rowley et al 1998;Sellers et al 2006), reduced psychological symptoms, particularly depression and anxiety (Sellers et al 2006), and higher levels of academic achievement (Altschul et al 2006;Jagers et al 1997;Wong et al 2003). Racial identity seems to serve as a buffer for acts of racism, discrimination, or prejudice (Greene et al 2006).…”
Section: Gendered Racial Identity Of Black Young Womenmentioning
confidence: 99%
“…This refers to the importance of emotional expressiveness and of being in tune with the feelings and emotional needs of others . Research with African Americans has shown that affect sensitivity is a predictor of empathy, a factor associated with prosocial behavior . The protective effects of emotional expressiveness on physical and mental health outcomes has also been documented .…”
Section: Cultural Considerationsmentioning
confidence: 99%